2019
DOI: 10.1016/j.ecolecon.2019.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations in contributors to life satisfaction: An Australian case study

Abstract: NonCommercial-NoDerivatives international license (CC BY-NC-ND 4.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…We found that the percentage of people suffering decreased from 3.32 to 2.68% and those struggling decreased from 11.29 to 9.77% over the past 17 years, while those thriving increased from 85.39 to 87.64% over this period. This implies that in Australia, inequality of LS has decreased slightly over time [44]. The fact that the inequality of LS has decreased in Australia shows that previously implemented policies have been successful to some extent in improving the LS for many.…”
Section: Inequality Of Life Satisfactionmentioning
confidence: 96%
See 3 more Smart Citations
“…We found that the percentage of people suffering decreased from 3.32 to 2.68% and those struggling decreased from 11.29 to 9.77% over the past 17 years, while those thriving increased from 85.39 to 87.64% over this period. This implies that in Australia, inequality of LS has decreased slightly over time [44]. The fact that the inequality of LS has decreased in Australia shows that previously implemented policies have been successful to some extent in improving the LS for many.…”
Section: Inequality Of Life Satisfactionmentioning
confidence: 96%
“…This means that these individuals are more susceptible to life events impacting their LS, both positively and negatively. If their LS can be impacted positively, opportunities exist for targeted policies to improve overall LS of communities that are struggling [44,45]. Identifying factors that detract from those individuals' lives or communities, and making even minor interventions in addressing those issues, could have significant impacts on the LS of the entire Australian community.…”
Section: Average Life Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decades, survey-research methods introduced by the social sciences have brought a breakthrough. Until now, indicators have been categorized in one of three ways: (1) those that adjust economic indicators to include social and environmental aspects, (2) those that measure quality of life or life satisfaction directly through surveys, and (3) those that are composite indicators bringing together a multitude of (Kubiszewski, Jarvis, & Zakariyya, 2019).…”
Section: Happinessmentioning
confidence: 99%